Efecto de diferentes niveles de presión arterial media sobre la perfusión tisular en el manejo de pacientes con shock séptico - Salazar Rodríguez, Anthony Eder (2014)
Severe sepsis and septic shock represent major requirements for managers of health. Models of septic shock resuscitation show that tissue perfusion (TP) is altered even though the systemic hemodynamics and regional standardization. Therefore early strategy of detection and treatment with quantitative goals within the first hours decreases the mortality rate. One way to improve tissue perfusion is the increase in mean arterial pressure (MAP). Therefore we try to determine what would be the optimal levels of MAP in the management of septic shock to improve TP. Objectives: To determine which levels of mean arterial pressure are more effective in improving lactate levels and urine output six hours after the management of septic shock with norepinephrine. Methods: An observational prospective cohort study, which was considered as showing the entire population that met the inclusion criteria was performed. We classified patients according to rank achieved average MAP and subsequent to that the effect of MAP on the TP through the variation of lactate level and urine output was determined. Results: 23 patients were captured: 8 reached MAP 65-75 mmHg (cohort 1), 8 reached MAP 75-85 mmHg (Cohort 2) and 7 reached MAP 85-95 mmHg (cohort 3). More effectively to reduce the level of lactate in cohort 2 when compared with group 1 and 3, was found significantly. The reduced levels of lactate in cohorts 1, 2 and 3 were 19.09, 32.38 and 15.00% respectively. No more effectively in any other cohort was found to preserve urine output. Urine output reached in Cohorts 1, 2 and 3 were 33.33, 50 and 28.33 ml / h, respectively. Conclusions: An average blood pressure of 75-85 mmHg compared to 65-75 mmHg and 85-95 mmHg as a management objective in patients with septic shock had higher efficiency to decrease lactate level significantly and to preserve urine output not significantly